TEACHING METHODS AND INSTRUCTIONAL MATERIALS AS PREDICTORS OF STUDENT SATISFACTION IN ENGLISH FOR HOTEL AND TOURISM COURSE - Widya Syafitri; Elsi Amiza; Khairiyati Wazaki (JEE (Journal of English Education), 2026)
Student satisfaction is increasingly recognised as a key measure of instructional quality in English for Specific Purposes (ESP), yet empirical studies examining its predictors in tourism education remain scarce. This study investigates how teaching methods and teaching materials relate to student satisfaction in an English for Hotel and Tourism course at a Indonesian Islamic university. Using a quantitative correlational design, data were gathered from 23 students within a small sample context through a Likert-scale questionnaire. Non-normal data distribution (Kolmogorov–Smirnov and Shapiro–Wilk, p < 0.05) warranted the use of Spearman Rank Correlation and Multiple Correlation Analysis. Results show strong correlations between teaching methods and student satisfaction (r = 0.829, p < 0.05), between teaching materials and student satisfaction (r = 0.788, p < 0.05), and a combined effect of R = 0.838. These findings indicate that contextualized pedagogy and industry-relevant materials are decisive drivers of learner satisfaction, with implications for ESP curriculum design in vocational tourism education.